What Can We Learn From the History of Homosexuality in Russia? - Healey, Dan (History compass, 2003)
Since the collapse of the Soviet regime in 1991, scholars have generated a wave of new studies on the political, social and cultural history of Russia, making enthusiastic use of sources that were once inaccessible. Topics long taboo under the pall of Cold War conservatism (in the West) and authoritarian censorship (in the East) are also increasingly open to researchers too.1 The history of homosexuality in Russia is one such topic.